Activation of Pneumocystis carinii infections in experimentally immunosupressed laboratory mice - Özer, Edip; Eröksüz, Yesari; Eröksüz, Hatice; Şaki, Cem Ecmel (Scientific and Technical Research Council of Turkey, 1996)
This study was performed on 40 laboratory mice, divided into four different group including ten mice in each. The groups were arranged as two controls (Groups 1 and 4) and two experimental groups (Groups 2 and 3). On the first day of experiments, mice in group 1 were sacrificed to determine latent infection in the animals. On the second group animals, splenectomy was performed and animals were sacrificed 10 days after splenectomy. Third group served as dexamethasone + tetracycline test group. These animals were given 1 mg/lt dexamethasone and 0.5 gr/lt tetracycline in drinking water for 2.5 month. Third group animals were sacrificed at the end of this immunosuppression period. Fourth group animals were also used as the control group and were sacrificed at the end of experiments. In corticosteroid and tetracycline group, animals exhibited significant clinical and macroscopic changes during the observation period and at necropsy whereas in other groups no changes were noticed. In all the animals, necropsy was performed and impression slides were prepared from the lung tissues. After toluidine blue O (TBO) staining, Pneumocystis carinii, trophozoid, precyst and cysts were searched in these slides. Accordingly, in control group animals 10 % of the tissues contained various developmental forms of P. carinii. In splenectomized and corticosteroid plus tetracycline groups, these percentages were 50 (5 animals) and 30 (3 animals) respectively. Hematoxylin and eosin staining of the lung tissues in paraffin sections from infected animals showed that interstitial tissues were increased and in some alveoles, eosinophilic exudate with honeycomb apperence was present. In the exudation, alveolar macrophages and scattered plasma cells were noticed. The lung tissue sections were also stained with Gomori's methanamine silver (GMS). In infected test group animals, it was determined that interalveolar and intraalveolar tissues contained parasitic cysts. In control animals neither parasitic cysts nor morphological changes were observed.
Deneysel Olarak Immun Sistemi Baskilanmiş Laboratuvar Farelerinde Pneumocystis carinii Enfeksiyonunun Geliştirilmesi ve Morfolojik De?işiklikler
Keywords: Mice; Pathology; Pneumocystis carinii